Aryl hydrocarbon receptor: The master regulator of immune responses in allergic diseases - Riaz, Farooq; Pan, Fan; Wei, Ping (Frontiers in Immunology, 2022)
The aryl hydrocarbon receptor (AhR) is a widely studied ligand-activated cytosolic transcriptional factor that has been associated with the initiation and progression of a variety of diseases, including autoimmune diseases, cancers, metabolic syndromes, and allergies. Generally, in a canonical signaling manner, AhR responds and binds to environmental toxins/ligands, such as dietary ligands, microbial ligands, xenobiotic ligands, or ecological allergens, and participates in regulating toxicological, biological, cellular, and responses. Activation of AhR is responsible for the increase in cytochrome P450 enzymes which help individuals to degrade and metabolize these environmental toxins and ligands. However, canonical signaling cannot be applied to all the effects mediated by AhR. Recent findings indicate that activation of AhR signaling also interacts with some non-canonical factors like Kruppel-like-factor-6 (KLF6) or estrogen-receptor-alpha (Erα) to affect the expression of downstream genes. Most importantly, enormous reseach has been conducted to evaluate the effect of AhR signaling on innate and adaptive immunity. It has been shown that AhR exerts numerous effects on antigen-presenting cells (APCs), Th1/Th2 cell balance, Th17, and regulatory T cells; thus, playing a significant role in allergens-induced diseases. This review discussed how AhR mediates immune responses in allergic diseases. Meanwhile, we believe that understanding the role of AhR in immune responses will not only enhance our knowledge of AhR-mediated immune regulation in allergic diseases but also help us understand the role of AhR in regulating immune responses in autoimmune diseases, cancers, metabolic syndromes, and infectious diseases.